A latent invader: transcriptomics reveals Cercospora zeina’s stealth infection strategy of maize and immune-activating effectors - Nadasen, Trystan; Buitendag, Carla; Visser, Rodé; Welgemoed, Tanya; Hein, Ingo; Berger, Dave Kenneth (Frontiers in Plant Science, 2025)
Cercospora zeina is a fungal pathogen that causes gray leaf spot (GLS) disease on maize (Zea mays L.). Upon landing on a leaf, the pathogen enters through the stomata and continues to develop asymptomatically for up to 28 days before symptoms appear. As previous work has yet to adequately determine how the pathogen behaves during its infective period, we used transcriptomics to gain insights about the in-planta development of the pathogen and explore its use of effectors to facilitate this process. Samples from B73 maize inbreds inoculated with an African reference strain of C. zeina (CMW25467) were harvested in a time course experiment and used for deep RNA sequencing. We used reads mapped to an improved assembly and annotation of the C. zeina CMW25467 genome as a proxy for biomass accumulation. Following the latent period, C. zeina was found to rapidly accumulate biomass and showed a nearly 50-fold increase in biomass as symptoms appeared. Two distinct transcriptional waves occurred across the infection period. The first wave showed expression of genes for cellular growth, maintenance and immune avoidance, whereas the second wave was enriched with genes involved in detoxification and carbohydrate catabolism. A total of 140 putative effector genes were differentially expressed over the time course, with most upregulated during the mid stage when the switch to necrotrophy occurred. Transient expression of three of these C. zeina effectors (CzEcp2, CzNIS1a, CzNIS1b) induced plant immunity in Nicotiana spp. resulting in the development of cell death. The CzNIS1a effector required a signal peptide for activity in Nicotiana benthamiana, indicating that it is most likely secreted into the apoplast for this function. The previously undescribed CzNIS1b family member has an N-terminal domain with high sequence and structural identity to CzNIS1a plus a C-terminal domain made up of four alpha helices. Orthologues of CzNIS1b appear to be limited to the Mycosphaerellaceae. This study suggests that a cohort of C. zeina effectors expressed during the mid-stage of infection have functions for which receptors are present in non-host species like tobacco. Altogether, this work suggests C. zeina behaves as a latent necrotroph and provides a foundation for future research into the infection biology of C. zeina.